POLA KOMUNIKASI DUA ARAH ANAK SLOW LEARNER TIPE DISGRAFIA DI SDN BALARAJA 03 - Puspaningtyas, Anindya; Yuliana, Rina; Fajrudin, Lili (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
Dysgraphia is a type of learning disorder that affects children’s writing abilities. Difficulties in writing can impact students’ psychological well-being, hinder their academic achievement, and interfere with their social skills. For children with dysgraphia who experience writing difficulties, verbal communication can be used as a means to express messages, opinions, and ideas. In addition, nonverbal communication can also be utilized when verbal communication skills are still limited. This study aimed to examine teachers’ lesson planning, the implementation and outcomes of two-way communication patterns among slow learners with dysgraphia during the learning process, as well as to identify the challenges and obstacles in such communication. The research employed a qualitative case study method. The subject of the study was a child with dysgraphia. Data were collected through observation, interviews, and documentation. Data analysis followed the Miles and Huberman model. The findings showed that children with dysgraphia more frequently used nonverbal communication with teachers and classmates, such as clapping and nodding. However, they also used verbal communication, although their speech was not very loud.